Associations between periods of COVID-19 quarantine and mental health in Canada. (January 2021) - Daly, Zachary; Slemon, Allie; Richardson, Chris G.; Salway, Travis; McAuliffe, Corey; Gadermann, Anne M.; Thomson, Kimberly C.; Hirani, Saima; Jenkins, Emily K.
Highlights: Adverse mental health outcomes due to COVID-19 quarantine vary by reason for quarantine Quarantine is associated with suicidal thoughts except when done due to recent travel Quarantine surveillance should include active mental health assessment and outreach Individuals who have quarantined during the COVID-19 pandemic are at increased risk for adverse mental health consequences beyond the quarantine period itself and should receive "flagged" for ongoing mental health monitoring Abstract: Since the onset of the COVID-19 pandemic, many jurisdictions, including Canada, have made use of public health measures such as COVID-19 quarantine to reduce the transmission of the virus. To examine associations between these periods of quarantine and mental health, including suicidal ideation and deliberate self-harm, we examined data from a national survey of 3000 Canadian adults distributed between May 14-29, 2020. Notably, participants provided the reason(s) for quarantine. When pooling all reasons for quarantine together, this experience was associated with higher odds of suicidal ideation and deliberate self-harm in the two weeks preceding the survey. These associations remained even after controlling for age, household income, having a pre-existing mental health condition, being unemployed due to the pandemic, and living alone. However, the associations with mental health differed across reasons for quarantine; those who were self-isolating specifically due to recent travel were not found to have higher odds of suicidal ideation or deliberate self-harm. Our research suggests the importance of accounting for the reason(s) for quarantine in the implementation of this critical public health measure to reduce the mental health impacts of this experience.